PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA KEBERAGAMAN MAKHLUK HIDUP DILINGKUNGANKU - Syifa Nanda Camilla; Iyan Irdiyansyah, Nur Hikmah (STKIP Subang, 2026)
This study aims to determine the effect of the model Problem Based Learning on the learning outcomes of the sub-theme of diversity of living things in my environment in class IV students of Limusnunggal 02 State Elementary School, Cileungsi District, Bogor Regency. This type of research is a quasi-experimental. The population consists of class IV-A and IV-C consisting of 56 people. The research was conducted in two meetings in each class group. Simple random sampling with lottery system is used to select sample of this research. Data analysis was performed with the n test gain, normality test, homogeneity test as a prerequisite test before conducting a hypothesis test (t test). the results of data analysis obtained t-count (4.575) > t-table (2.004) for a significant 5%. Based on the test criteria, H0 rejected and Ha accepted. Based on the results of these studies it can be concluded that there is influencemodel Problem Based Learning on learning outcomes.